Musical and Phonetic Training for Bilingual Education - Gutiérrez Sandoval, Pavel Roel (Atenas, 2016)
Need to move from the traditional method to learn English to music education strategies and applied phonetics. Since the creation of the Technical Experimental Unit Conacyt-UACJ 2015, it has impacted the training for students of the bachelor in education. The project capacitated they in the use of scientific equipment for the analysis of the phonetic and phonological skills to 10 students who teach English to girls/boys in elemental schools, who speak Spanish as their native language, to include effective teaching strategies to support classroom environment to learn to compare, understand or pronounce the individual phonemes and identify suprasegmental features of English-Spanish.